History and historians in the XXI century - Pérez Herrero, Pedro; Escribano Roca, Rodrigo (EUNOMÍA. Revista en Cultura de la Legalidad, 2021)
The mission of this text is to explain why History has ceased to have in the last three decades the public presence and persuasive power that it had during the 19th century and the first half of the 20th century. We propose that History should articulate plural stories in order to generate a better intercultural connection in the global world in which we live and to overcome exclusive nationalist stories.
Keywords: History, modernity, plurality, historians, XXIst century, globalization, interculturality